The via squeeze. - Lassen, C.L (IEEE spectrum)
Already less than 150 μm in diameter, vias can no longer be economically produced by mechanical drilling, as are conventional throughholes. Instead, they must be made by such alternative processes as laser ablation or the photochemical etching of thin dielectrics built up on either side of a conventional circuit board core. The new microvias are electrical paths less than 0.1 mm in diameter running between one layer of the circuit board structure and another. The first major change in the technology in 30 years, microvias are gaining momentum and pushing the printed-circuit industry to use new materials and new processes